Reproductive performance of singleton and twin female offspring born to ewe-lamb dams and mature adult dams - Loureiro, MFP; Kenyon, PR; Pain, SJ; Blair, HT (New Zealand Society of Animal Production)
This study was undertaken to compare the reproductive and live weight performance of female singleton and twin ewes born to either mature or young dams from 18 months to 2.5 years of age. One hundred and fifteen singleton- and twin-born female offspring born to either ewe-lamb (8 months at breeding) or adult ewe dams were maintained as one cohort under commercial New Zealand grazing conditions. Ewe live weights and body condition scores were recorded, as were ovulation rates at a synchronised breeding and number of fetuses present at pregnancy scanning. The live weight of ewes born to ewe-lambs were lighter (P<0.05) than those born to adult ewes at breeding and during their first pregnancy but not (P>0.05) at the weaning of their lambs. Twin-born ewes were lighter (P<0.05) than their singleton-born counterparts. There was no difference in corpora lutea number (P>0.05) at breeding or number of fetuses at pregnancy scanning. Lambs whose grand dam was a ewe-lamb were heavier at birth (P<0.05) but not at weaning (P>0.05) compared to those lambs whose grand dams was an adult ewe. This data suggests there are few negative impacts from selecting progeny born to ewe lambs as replacement ewes. However, before this hypothesis can be supported, lifetime data of these ewes needs to be collected.
Keywords: ewe lamb; hoggett; reproductive performance; mature ewe; 0702 Animal Production